La comunicación social - Quezada, Maribel (Revista Chilena de Humanidades, 2015)
Professor Quezada states and examines the problem of the limits and the comprehension of subject matter proper to the discipline which is concern ed with social communication. In this respect obj ectives, conceptualization, methodology and application procedures current in the USA and in European countries through different periods are discussed, while establishing the fact that in Latin America the tendency has been rather to reproduce models, mainly American,than to adopt positions that would more adequately and appropiately respond to regional realities; and in the case of Chile, it would be necessary to expand significantly research in this field.